2004
DOI: 10.1242/dev.01070
|View full text |Cite
|
Sign up to set email alerts
|

The Cerberus/Dan-family protein Charon is a negative regulator of Nodal signaling during left-right patterning in zebrafish

Abstract: We have isolated a novel gene, charon, that encodes a member of the Cerberus/Dan family of secreted factors. In zebrafish, Fugu and flounder, charon is expressed in regions embracing Kupffer's vesicle,which is considered to be the teleost fish equivalent to the region of the mouse definitive node that is required for left-right (L/R) patterning. Misexpression of Charon elicited phenotypes similar to those of mutant embryos defective in Nodal signaling or embryos overexpressing Antivin(Atv)/Lefty1, an inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
189
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(202 citation statements)
references
References 60 publications
12
189
1
Order By: Relevance
“…We reproduced this effect with the aid of an FGF8 MO and showed that knockdown of Ier2 and Fibp1 phenocopies loss of FGF8 in this system. Either of these interventions also led to a loss of cha expression, providing an additional link to the establishment of laterality (39). Most critically, the effect of FGF8 knockdown on ciliogenesis and cha expression could be rescued by supplying Ier2 and Fibp1, indicating that FGF8 action in laterality establishment is mediated by these two factors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We reproduced this effect with the aid of an FGF8 MO and showed that knockdown of Ier2 and Fibp1 phenocopies loss of FGF8 in this system. Either of these interventions also led to a loss of cha expression, providing an additional link to the establishment of laterality (39). Most critically, the effect of FGF8 knockdown on ciliogenesis and cha expression could be rescued by supplying Ier2 and Fibp1, indicating that FGF8 action in laterality establishment is mediated by these two factors.…”
Section: Discussionmentioning
confidence: 97%
“…Double label fluorescence in situ hybridization of ier2 with fgf8 and with charon (cha), a marker for Kupffer's vesicle, shows colocalization of fgf8 and ier2 in Kupffer's vesicle, with cha limited to a horseshoe-shaped caudal region, as reported in ref. 39 (Fig. 6 C and D).…”
Section: Ier2 and Fibp1 Are Required For Ciliogenesis In Kupffer's Vementioning
confidence: 90%
“…Rather, Cerberus-related proteins are key regulators of Nodal signaling and play an important role in the establishment of left -right asymmetry in the vertebrate embryo (Rodriguez Esteban et al 1999;Yokouchi et al 1999;Zhu et al 1999;Hashimoto et al 2004;Marques et al 2004;Tavares et al 2007;Vonica and Brivanlou 2007).…”
Section: Cerberusmentioning
confidence: 99%
“…Probes used were preproinsulin, ipf1 (Milewski et al, 1998), glucagon, preprosomatostatin2 (called somatostatin2 in this study) (Argenton et al, 1999), trypsin (Biemar et al, 2001), islet-1 (Korzh et al, 1993), nkx2.2 (Barth and Wilson, 1995;Kudoh et al, 2001), pax6.2 (Nornes et al, 1998), foxa2 (Strahle et al, 1993;Odenthal and Nusslein-Volhard, 1998), sox32 (Dickmeis et al, 2001;Kikuchi et al, 2001), sox17 (Al-exander and Stainier, 1999), foxA2 (Strahle et al, 1993;Odenthal and Nusslein-Volhard, 1998), foxa1 (Odenthal and Nusslein-Volhard, 1998), prox1 (Glasgow and Tomarev, 1998), cha (Hashimoto et al, 2004), lefty1 (Bisgrove et al, 1999;Thisse and Thisse, 1999), spaw (Long et al, 2003), and pitx2 (Essner et al, 2000).…”
Section: Whole-mount In Situ Hybridization and Immunohistochemistrymentioning
confidence: 97%
“…4, Table 2). charon is a cerberus/ dan family member and inhibits nodal signaling during left-right asymmetry, with the zebrafish Nodal gene southpaw as a target (Hashimoto et al, 2004). charon expression initiates around 2-3 somite stage in the hypoblast of the tailbud.…”
Section: Expression Of Genes Involved In Generation Of Left-right Asymentioning
confidence: 99%